On the West Indian weevil genus Lachnopus Schönherr, 1840 (Coleoptera: Curculionidae: Entiminae): descriptions of six new species, a proposal for species-groups, and an annotated checklist - Girón, Jennifer C.; O’brien, Charles W.; Rose-Smyth, M. Christine (Zootaxa, 2018)
We here describe and illustrate six new species of the genus Lachnopus, the most taxonomically chaotic group of entimines in the Caribbean region. These species are Lachnopus cozumelus Girón & O’Brien, sp. nov. from Cozumel Island, Mexico, Lachnopus karphos Girón & O’Brien, sp. nov. from Mayaguana Island in the Bahamas, Lachnopus lucayanus Girón & O’Brien, sp. nov. from Eleuthera in the Bahamas and Providenciales in the Turks and Caicos Islands, Lachnopus petilusquamus Girón & O’Brien, sp. nov. from Eleuthera in the Bahamas, Lachnopus rhabdotus Girón & O’Brien, sp. nov. from Providenciales in the Turks and Caicos Islands and Lachnopus vanessablockae Girón & O’Brien, sp. nov. from the Cayman Islands. These constitute the first species of the genus described for each island group, and expand the geographical range of the genus, by including the Lucayan Archipelago, the Cayman Islands and Cozumel Island. Individuals of L. vanessablockae have been collected on the Cayman endemic banana orchid (Myrmecophila thomsoniana (Orchidaceae)), which represents the first reported occurrence of Lachnopus weevils as pollinators. In addition, we present an annotated checklist of the species of Lachnopus, including collecting localities, host plants, and biological notes obtained from the literature or collection data from labels of collections’ specimens. Lachnopus coffeae Marshall, 1922 is recorded for the first time for Grand Bahama, which appears to be an introduction associated with citrus from Puerto Rico. We also list the fossil species attributed to the genus. Comments on some morphological characters and their variation across the genus are included. Species-groups within the genus are proposed, including diagnostic features to recognize them. Some taxonomic conflicts found in collections are pointed out. This paper compiles fundamental information, and assembles a framework for future revisionary work on Lachnopus.